2002
DOI: 10.1046/j.1365-2567.2002.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C‐reactive protein and pentosan polysulphate on human complement activation

Abstract: SUMMARYComplement (C) activation is believed to play an adverse role in several chronic degenerative disease processes, including atherosclerosis, myocardial infarction and Alzheimer's disease. We developed several in vitro quantitative assays to evaluate processes which activate C in human serum, and to assess candidates which might block that activation. Binding of C-reactive protein (CRP) to immobilized cell surfaces was used as a tissue-based method of activation, while immunoglobulin G in solution was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The observed hemolysis in our studies confirmed that CRP-mediated complement-activation ends with consumption of terminal membrane attack complex (MAC). Though most of the reported CRP-mediated complement-activation is essentially limited to stage involving C1-C4 [73] some reports also suggested deposition of MAC by CRP [40,74]. Therefore, our results are consistent with these reports revealing CRP-complement activation by binding with erythrocyte-CRP.…”
Section: Discussionsupporting
confidence: 92%
“…The observed hemolysis in our studies confirmed that CRP-mediated complement-activation ends with consumption of terminal membrane attack complex (MAC). Though most of the reported CRP-mediated complement-activation is essentially limited to stage involving C1-C4 [73] some reports also suggested deposition of MAC by CRP [40,74]. Therefore, our results are consistent with these reports revealing CRP-complement activation by binding with erythrocyte-CRP.…”
Section: Discussionsupporting
confidence: 92%
“…The anti-inflammatory action of the pentosan polysulfate is not clearly understood. It is reported that PPS decreases lipopolysaccharide-mediated NF-κB activation, suppresses leukocyte elastase, and inhibits complement activity [16,17,18]. It has been demonstrated that PPS decreases tubulointerstitial inflammation and preserves renal function in 5/6 nephrectomized rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that PPS decreases lipopolysaccharide-mediated NFkB activation, suppresses leukocyte elastase and inhibits complement activity. [15][16][17] As PPS has been found to substantially decrease tubulointerstitial inflammation and preserve renal function in 5/6 nephrectomized rats, 18 we asked if the antiinflammatory effect of PPS reduced DN in aging mice, which develop severe nephropathy, including typical tubulointerstitial inflammatory lesions. We also tested the effect of PPS on high glucose, AGEs and TNF-a-stimulated inflammation in renal cells in vitro.…”
mentioning
confidence: 99%